Patients' safety in intensive care units in an academic hospital in Gauteng - Tlhola, Mphofu Agnes (My University, 2016)
The purpose of this study was to assess any deviations from protocols and standards of patients’ care in different constructs of nursing care and to compare the deviations with the level of nursing expertise in five ICUs of one Academic hospital in Gauteng in order to make recommendations for nursing practice, education and future research. The study was conducted at one university-affiliated, public sector tertiary hospital in Johannesburg in Gauteng Province. A quantitative, prospective non-experimental design by random application of Critical Nursing Situation Index (CNSI) was used to assess adherence to nursing protocols. This Instrument was developed and validated by Binnekade in 2001 to assess the rate of occurrence of observable nursing errors in Intensive Care Units in the Netherlands. Data was analysed with the use of descriptive and inferential and results were presented as frequencies, graphs, means and standard deviations. Kruskal-Wallis and Cronbach’s reliability coefficient were also used to test the reliability of the tool and relationship between various variables respectively. The statistical significance level was 0.05 (p<0.05). Regarding the 100 patients whose care was assessed, and out of the eight domains of care, basic ICU nursing care was found to be associated with most deviations in relation to recording of patient’s length and body weight (100%, n=100), risk of pressure sore assessment (77%, n=77) and keeping patient’s relatives records (55%, n=55). Six hourly fluid assessment (100%, n=100) and adequate adjustment of alarms for cardiac rhythm (60%, n=60) were also among the areas of care with more than half of the deviations. These two fall under fluid administration and care of the cardiac rhythm and circulation respectively. Moreover, there was a statistically significant difference in occurrence of deviations in fluid administration and nurse’s qualifications. Recommendations were made to address these deviations in relation to patient assessment, risk identification and record keeping all to ensure patient’s safety.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science in Nursing Johannesburg, 2016